Pengaruh Gaya Kepemimpinan, Komunkasi, dan Kinerja Pengurus Terhadap Loyalitas Organisasi (Studi Pada Organisasi Himpunan Mahasiswa Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Lisa Qotrunnada; Abdul Kodir Djaelani; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to determine the effect of Leadership Style, Communication, and Management Performance on Organizational Loyalty in the Student Association of Management Department, Faculty of Economics and Business, Islamic University of Malang. The variables used in this research are Loyalty variable (dependent variable), while the independent variables are Leadership Style, Communication, and Management Performance. The results of this study conclude that the variables of leadership style, communication, and management performance have a simultaneous effect on organizational loyalty of the Student Association Management Department, Faculty of Economics and Business, Islamic University of Malang.Keywords: Loyalty, Leadership Style, Communication, and Performance.